Relacionamentos interpessoais: A relevância da mutualidade bíblica para a edificação de uma comunidade cristã - David Ziemann, Marcus (Vox Scripturae - Revista Teológica Internacional, 2010)
The theme “interpersonal relationships” has become more and more relevant nowadays. The individualism, the utilitarianism and immediacy of present era have conducted people to be more and more artificial in their relationships. On the other hand, the researches in Human Science area show that people are seeking for more significant friendly relationships and groups with interests. In this kind of relationships, one factor that guides is the mutuality. Nevertheless, in the context of the Christian community both relationships and mutuality must be seen from the Scripture’s view. The human being was created to maintain relationships and to live in groups. On the New Testament, this community is the church, the body of Christ. Inside of it, the relationships happen in Christian communion dimension. The relationships sign is the agape love that comes from God and the fraternal love among brothers in faith. In this context, the biblical mutuality, known by the expression “one to another”, can be considered the essential feature of the interpersonal relationships. In practical terms, the relevance is connected to the Christian community edification. It makes the cult a space of fraternal celebration. It makes the teaching a discipleship space. It makes the community life a mutual service and mutual advice space. Finally, the Bible mutuality makes the interpersonal relationships relevant personal faith so that the community life edification the Christ Body.